The theological turn in youth ministry - Root, Andrew, 1974-; Dean, Kenda Creasy, 1959- (Downers Grove, IL : IVP Books, 2011)
Andrew Root and Kenda Creasy Dean invite us to envision youth ministries full of practical theologians, addressing the deep questions of life with a wonderfully adolescent mix of idealism, cynicism and prophetic intolerance for hypocrisy. The result is a more rigorous and meaningful youth ministry, and a more theologically grounded and engaged church.
Part 2 : theology enacted : exploring youth ministry practice -- Is Jesus magic? : healing and the cross in youth ministry / Andrew Root -- Talking about sin with young people / Andrew Root -- Holding on to our kisses : the hormonal theology of adolescence / Kenda Creasy Dean -- The eschatological significance of summer camp / Kenda Creasy Dean -- What are we doing in these mountains? : the outdoor trip and the theology of the cross / Andrew Root -- The mission trip as global tourism : are we ok with this? / Andrew Root -- Doubt and confirmation : the mentor as co-doubter / Andrew Root -- Ascension deficit disorder : youth ministry as a laboratory for hope / Kenda Creasy Dean -- Postscript : reflecting on method : youth ministry as practical theology / Andrew Root with Blair D. Bertrand.
Includes bibliographical references.
Keywords: Church work with youth; Theology -- youth ministry